PD-1 and LAG-3 expression in EBV-associated pediatric Hodgkin lymphoma has influence on survival - Jimenez, Oscar; Mangiaterra, Tamara; Colli, Sandra; García Lombardi, Mercedes; Preciado, Maria Victoria; De Matteo, Elena; Chabay, Paola (Frontiers in Oncology, 2022)
In pediatric Hodgkin lymphoma (HL), the inability of the cytotoxic microenvironment induced by EBV presence to eliminate tumor cells could reflect the fact that the virus might be able to induce the expression of exhaustion markers to evade an immune response. Therefore, the expression of exhaustion markers in pediatric EBV–associated HL was evaluated. A balance between cytotoxic GrB and Th1 Tbet markers with regulatory Foxp3 was proved in EBV+ cases. In addition, exclusively in EBV-associated cHL, a correlation between PD-1 and LAG-3 expression was observed. Furthermore, those cases also displayed a trend to worse survival when they expressed LAG-3 and inferior event-free survival when both PD-1 and LAG-3 molecules were present. Therefore, even though a cytotoxic and inflammatory environment was supposed to be triggered by EBV presence in pediatric cHL, it seems that the virus may also induce the synergic effect of inhibitory molecules LAG-3 and PD-1 in this series. These observations may reflect the fact that the permissive and exhausted immune microenvironment succeeds to induce lymphomagenesis.